Tuning of Electron States of Transition Metal’s Catalysts Using Acceptor’s Atoms: ab initio Calculation - R.M. Balabai; D.Yu. Gritsulia; V.G. Litovchenko (Журнал нано- та електронної фізики)
Within the methods of density functional theory and ab initio pseudopotential, we have obtained the spatial distributions of the density of valence electron and the electronic energy spectrum for the small clusters from the atoms of Cu, Ni, Co, O, Si with the aim to determine the mechanisms of their high catalytic activity. Electron’s levels of catalyst guide course of chemical reaction. We explored, that the organization of electronic states of nanocatalysts on the basis of transition metals possible control by changing the spatial organization of clusters and adding electronegative atoms.